Laparoscopic sleeve gastrectomy versus endoscopic sleeve gastroplasty: a systematic review and meta-analysis - Marincola, Giuseppe; Gallo, Camilla; Hassan, Cesare; Sessa, Luca; Raffaelli, Marco; Costamagna, Guido; Bove, Vincenzo; Pontecorvi, Valerio; Orlandini, Beatrice; Boškoski, Ivo (Endoscopy International Open, 2021)
Background and study aims Laparoscopic sleeve gastrectomy (LSG) is the current standard for bariatric surgery, but it is affected by several postoperative complications. Endoscopic sleeve gastroplasty (ESG) was created as a less invasive alternative to LSG. However, its efficacy and safety compared with LSG is unclear.Materials and methods Relevant publications were identified in MEDLINE/Cochrane/EMBASE/OVID/ PROSPERO and NIH up to January 2020. Studies were selected that included obese patients with a baseline body mass index (BMI) between 30 and 40 kg/m² with a minimum of 12 months of follow-up and with reported incidence of complications. The mean difference in percentage of excess weight loss (%EWL) at 12 months between LSG and ESG represented the primary endpoint. We also assessed the difference in pooled rate of adverse events. The quality of the studies and heterogeneity among them was analyzed.Results Sixteen studies were selected for a total of 2188 patients (LSG: 1429; ESG: 759) with a mean BMI 34.34 and 34.72 kg/m² for LSG and ESG, respectively. Mean %EWL was 80.32 % (± 12.20; 95 % CI; P = 0.001; I² = 98.88) and 62.20 % (± 4.38; 95 % CI; P = 0.005; I² = 65.52) for the LSG and ESG groups, respectively, corresponding to an absolute difference of 18.12 % (± 0.89; 95 % CI, P = 0.0001). The difference in terms of mean rate of adverse events was 0.19 % (± 0.37; 95 %CI; χ 2  = 1.602; P = 0.2056).Conclusions Our analysis showed a moderate superiority of LSG versus ESG. No difference in terms of safety was shown between the two groups. ESG is a less-invasive, repeatable and reversable and acceptable option for mild-moderate obese patients.